Enzymatic activity and chlorophyll fluorescence imaging of maize seedlings (Zea mays L.) after exposure to low doses of chlorsulfuron and cadmium - Li-juan ZHAO; Jing-fang XIE; Hong ZHANG; Zhen-tao WANG; Hong-jin JIANG; Shao-long GAO (Journal of Integrative Agriculture, 2018)
The aim of this research was to study the influence of chlorsulfuron residue and cadmium on the enzymatic activity and photosynthetic apparatus of maize (Zea mays L.) plants. Chlorsulfuron and cadmium at 0.001 and 5.0 mg kg−1, respectively, were mixed and applied to soil prior to planting. The levels of chlorsulfuron- and cadmium-induced stress to plants were estimated by growth, chlorophyll content, lipid peroxide content, enzyme activities, and major fluorescence parameters of chlorophyll (revealed by the fluorescence imaging system FluorCam). Chlorsulfuron negatively affected the chlorophyll content, photochemical efficiency of photosystem II in the dark-adapted state, the maximum efficiency of photosystem II, photochemical quenching coefficient, and steady-state fluorescence decline ratio in the leaves of maize seedlings. However, cadmium did not produce noticeable changes. Plants that were exposed to both chlorsulfuron and cadmium showed an obvious increase in the steady-state fluorescence decline ratio. These results implied that the seedlings possessed more resistance to cadmium than to chlorsulfuron and their resistance to chlorsulfuron toxicity was enhanced by the presence of cadmium. The results also suggested that chlorophyll fluorescence imaging reveals overall alterations within the leaves but may not reflect small-scale effects on tissues, as numeric values of specific parameters are averages of the data collected from the whole leaf.